2020
DOI: 10.1530/joe-20-0052
|View full text |Cite
|
Sign up to set email alerts
|

Insulin sensing by astrocytes is critical for normal thermogenesis and body temperature regulation

Abstract: The important role of astrocytes in the central control of energy balance and glucose homeostasis has only recently been recognized. Changes in thermoregulation can lead to metabolic dysregulation, but the role of astrocytes in this process is not yet clear. Therefore, we generated mice congenitally lacking insulin receptors (IR) in astrocytes (IRKOGFAP mice) to investigate the involvement of astrocyte insulin signaling. IRKOGFAP mice displayed significantly lower energy expenditure and a strikingly lower basa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 90 publications
(103 reference statements)
1
11
0
Order By: Relevance
“…Normally, this ratio falls between a value of 0.7 and 1.0, wherein a reading near 0.7 indicates the mice are primarily using fatty acid metabolites for energy production, whereas a reading near 1.0 suggests carbohydrate usage. 29 , 30 At 5 and 15 weeks after HFD, both the NLC and βARKnt mice showed comparable O 2 consumption (V o 2 ) ( Supplemental Figures S3A to S3H ) and CO 2 production (VC o 2 ) ( Supplemental Figures S3I to S3P ) at a normothermic condition (30°C) and room temperature (22°C), as well as during cold challenge (4°C). Interestingly, the RER was significantly different between groups ( Figure 2A ), wherein it was significantly elevated during the normothermic condition ( Figure 2B ), unchanged at room temperature ( Figure 2C ), and reduced during cold challenge ( Figure 2D ) in both the light and dark cycles in the βARKnt compared with control mice after 5 weeks of HFD stress.…”
Section: Resultsmentioning
confidence: 99%
“…Normally, this ratio falls between a value of 0.7 and 1.0, wherein a reading near 0.7 indicates the mice are primarily using fatty acid metabolites for energy production, whereas a reading near 1.0 suggests carbohydrate usage. 29 , 30 At 5 and 15 weeks after HFD, both the NLC and βARKnt mice showed comparable O 2 consumption (V o 2 ) ( Supplemental Figures S3A to S3H ) and CO 2 production (VC o 2 ) ( Supplemental Figures S3I to S3P ) at a normothermic condition (30°C) and room temperature (22°C), as well as during cold challenge (4°C). Interestingly, the RER was significantly different between groups ( Figure 2A ), wherein it was significantly elevated during the normothermic condition ( Figure 2B ), unchanged at room temperature ( Figure 2C ), and reduced during cold challenge ( Figure 2D ) in both the light and dark cycles in the βARKnt compared with control mice after 5 weeks of HFD stress.…”
Section: Resultsmentioning
confidence: 99%
“…24 On the other hand, energy expenditure has recently been associated with astrocytic insulin signalling. 43 Mice with a constitutive ablation of IR in astrocytes exhibited decreased energy expenditure and reduced body temperature both with respect to ad libitum fed and upon fasting without any changes in total body weight. Such impairments in thermogenesis were linked to lower sympathetic innervation of brown adipose tissue, which exhibited morphological abnormalities such as increased lipid droplets.…”
Section: Box 1 Astrocytic Control Of Synaptic Functionmentioning
confidence: 99%
“…Such impairments in thermogenesis were linked to lower sympathetic innervation of brown adipose tissue, which exhibited morphological abnormalities such as increased lipid droplets. 43 Importantly, however, these changes that were observed upon congenital ablation of astrocytic IR were absent in a mouse model that allowed for postnatal IR ablation using tamoxifen-mediated induction, 24 thus raising the possibility that the astrocyte-specific loss of insulin signalling throughout development leads to permanent changes in the homeostatic neurocircuitry regulating body temperature. 43 Therefore, the effect of insulin signalling in astrocytes on metabolic function and thermogenesis could depend on the time of astroglial IR ablation.…”
Section: Box 1 Astrocytic Control Of Synaptic Functionmentioning
confidence: 99%
“…228 Although there is a growing recognition of the role of insulin signalling within CNS astrocytes in the regulation of food intake, there has been little examination of a role in adipose tissue thermogenesis. Recently, Manaserh et al 229 showed that INSR deletion in astrocytes reduced BAT thermogenesis and BAT β3-adrenergic receptor expression. Because these mice could not engage a thermogenic response to cold exposure, this implies a functional role of astrocytic INSR signalling in thermogenesis.…”
Section: Insulin Signalling In the Brain Regulates Energy Expenditurementioning
confidence: 99%
“…Many of these actions are mediated by insulin signalling in AgRP and POMC neurones in the ARC. Emerging evidence now substantiates novel insulin-responsive neuronal and non-neuronal subsets in the hypothalamus 44,101,149,152,229 ; however, the functional contribution of this signalling is still in its infancy. Beyond the hypothalamus, insulin is known to regulate cells within areas of the brain involved with reward, 160,161,163,204 olfaction 198,199 and stress.…”
Section: Con Clus Ionsmentioning
confidence: 99%